2014
DOI: 10.1016/j.jfma.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the diagnostic accuracy of ultrasonography in assessing the severity of hepatic steatosis

Abstract: Ultrasonography could assess the severity of hepatic steatosis with moderate accuracy. Obese patients are difficult ultrasonographically. In addition, age and hepatic fibrosis could affect the performance of ultrasonography in assessing the severity of hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…Our data are consistent with previous reports which compared ultrasound against histology, MRS or other imaging techniques, suggesting that ultrasound is a valid method to diagnose hepatic steatosis [ 7 , 25 27 , 31 , 37 ]. However, other studies have reported that the sensitivity may decrease in obese and older patients [ 38 40 ] perhaps because thick layers of subcutaneous fat may limit the ability to reliably detect liver echogenicity[ 39 ] or ageing may change the echo properties of the liver and kidney[ 40 ]. However, our observations demonstrate that the ultrasound method used here has excellent validity even in a sample of older individuals with a high prevalence of overweight and obesity (overweight 49% and obese 15%).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with previous reports which compared ultrasound against histology, MRS or other imaging techniques, suggesting that ultrasound is a valid method to diagnose hepatic steatosis [ 7 , 25 27 , 31 , 37 ]. However, other studies have reported that the sensitivity may decrease in obese and older patients [ 38 40 ] perhaps because thick layers of subcutaneous fat may limit the ability to reliably detect liver echogenicity[ 39 ] or ageing may change the echo properties of the liver and kidney[ 40 ]. However, our observations demonstrate that the ultrasound method used here has excellent validity even in a sample of older individuals with a high prevalence of overweight and obesity (overweight 49% and obese 15%).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Wang et al [34], the agreement rates between US and the histological findings were 74.3% in assessing the presence of steatosis and 61.4% in assessing steatosis severity. By using univariate analyses, body mass index (BMI) and necroinflamatory activity were associated with agreement between US and histology.…”
Section: Factors Influencing the Us Performance In Detecting Steatosismentioning
confidence: 93%
“…For example, US in morbidly obese patients had the lowest accuracy and advanced fibrosis can reduce the sensitivity of US [30]. Regarding the relationship between age and the diagnostic accuracy of US, the possible explanation was that the aging process could change the echo texture of liver and/or kidney, and thus lead to a poor performance of US in older populations [34].…”
Section: Factors Influencing the Us Performance In Detecting Steatosismentioning
confidence: 99%
“…Conventional US is an accurate and highly reliable diagnostic tool for steatosis assessment. Wang et al [28] found that the agreement rate of US as compared to histology is 61.4% in assessing the steatosis severity and 74.3% in diagnosing steatosis. A meta-analysis by Hernaez et al [22] estimated that the US sensitivity to detect moderate and severe steatosis confirmed by histology is 84.8% and the specificity is 93.6%.…”
Section: Us Performance For Steatosis Detectionmentioning
confidence: 99%